Analysis of the Implementation of the National Planning System According to Law Number 25 of 2004 in Indonesia - cahya, Silvia; Fahri Fauzi Rahman; Ludiana; Indri Apriyanti (GoResearch - Research & Publishing House, 2024)
The background of this research is that to achieve sustainable growth and development, every country needs good and effective planning. The development planning system in Indonesia has been stated in the governing law, namely law number 24 of 2004. This law establishes the framework, process, and mechanism in the preparation and implementation of national planning covering various development sectors. The research aims to find out how to analyze the implementation of the national planning system according to Law Number 25 of 2004 in Indonesia. This research uses a qualitative approach with descriptive methods. The type of data used is secondary data. Data collection techniques using literature studies or literature. The data analysis technique used in this research is SWOT analysis technique. The results show that the implementation of the national development planning system according to law number 25 of 2004 in the strength indicators there is a strong legal basis, the weakness indicators that the emphasis of development law is still at the normative or regulative level only, opportunities that Indonesia has with advances in information technology that can support the development planning process, and threats faced in implementing it there are limitations in resources and budgets.